Pengaruh Content Marketing dan Influencer Marketing terhadap Keputusan Pembelian Handphone Vivo: Studi Kasus Konsumen Handphone Vivo Kota Bengkulu - Chandra Aditya; Ade tiara Yulinda (ManBiz: Journal of Management and Business, 2024)
This research aims to determine the influence of content marketing and influencer marketing on Vivo cellphone purchasing decisions (case study of Vivo cellphone consumers in the city of Bengkulu). This research is quantitative research, the object of this research is Vivo cellphone consumers in the city of Bengkulu with a sample of 96 respondents, using a purposive sampling technique. Data was collected through questionnaires and analyzed using the multiple linear regression method. Based on the results of multiple linear regression, the regression equation Y = = 4.468 + 0.267 (X1) + 0.570 (X2) is obtained. The results of the hypothesis test show that content marketing has a significant influence on the decision to purchase a Vivo cellphone, with a significant level (0.007 < 0.050), and influencer marketing has a significant influence on the decision to purchase a Vivo cellphone, with a significant level (0.000 < 0.050), testing the hypothesis test f shows that content marketing and influencer marketing have a significant influence on Vivo cellphone purchasing decisions at a significant level (0.000 < 0.050). .This means that the results of the t test analysis state that the results are significant for all variables and the hypothesis is accepted. The results of multiple regression analysis also show a coefficient of determination of 0.432, which means that the content marketing and influencer marketing variables influence consumer purchasing decisions by 43.2%, while 56.8% is influenced by other variables not observed in this research.